Examining institutional credit access among agricultural households in Eastern India: trends, patterns and determinants. Issue 2 (3rd October 2020) - Kumar, Anjani; Das, Raya; K S, Aditya; Bathla, Seema; Jha, Girish K.
Abstract : Purpose: This paper is an attempt to understand the pattern of credit among agricultural households in Eastern India and to identify the correlates of their access to institutional credit for policy imperatives. Design/methodology/approach: The study uses unit-level data from the All-India Debt and Investment Survey of the 59th and 70th rounds of the National Sample Survey Office for the years 2002–2003 and 2012–2013. Cragg's double-hurdle model and the Heckman selection model are used to estimate the determinants of access to and the amount of institutional loans taken by households. These models also account for potential selection bias in the findings. Findings: The study reveals that access to credit is strongly associated with the socioeconomic and demographic characteristics of agricultural households. However, about half of the farmers in the eastern states of India lack access to institutional credit despite the government's attempts to include them in the ambit of formal financial services. Thus, strategies for developing agriculture in Eastern India must include efforts to bring small and marginal farmers under the coverage of institutional credit. Research limitations/implications: These data are based on the responses given by the sample households and not the experimental data. The data pertain to the year 2013. Originality/value: The findings emphasize that strategies for developing agriculture in Eastern India must give special push to enhance small and marginal farmers' access to institutional credit.